Selfgerigte tekskeuse vir Afrikaans Huistaal in die intermediêre fase met behulp van ŉ leesbaarheidsindeks [English translation: Self-directed text selection for Afrikaans Home Language in the intermediate phase using a readability index] - Du Plessis, Carmen; Vos, Elize (Journal for language teaching, 2022)
Well-developed reading comprehension skills are emphasized across the National Curriculum and Assessment Policy Statements (CAPS) of South Africa (DBE, 2011) as sufficient reading comprehension skills are central to successful learning in all subjects. Despite the high importance of effective reading and comprehension skills, the reading standard of intermediate phase learners remains alarmingly low when considering the results of international reading assessments. From these results, it becomes clear that learners do not have adequate reading comprehension when they are assessed on the content of a reading text. Although clear criteria for text selection do exist, the cause of poor reading comprehension can possibly be attributed to inappropriate text selection. For this article, the readability level of prescribed texts as a possible obstacle was examined. Various readability indices were investigated, specifically, those that can be used for Afrikaans Home Language to measure textual complexity. The readability of texts in home language textbooks (intermediate phase) was calculated. The investigation was approached from interpretivism and is qualitative in nature. Firstly, an extensive literature review was launched into the reading situation regarding intermediate phase learners, texts, criteria for text selection, text readability, and readability indices. Secondly, the CAPS (Afrikaans Home Language, intermediate phase) was analysed to determine what the guidelines for texts, text selection and readability entail. Finally, CAPS-accredited textbooks were analysed to determine the readability levels of some texts in them. The overarching themes that arose from the research data were used to make possible suggestions for Afrikaans Home Language teachers and textbook compilers regarding self-directed text selection for intermediate phase learners by using a readability index. Keywords: intermediêre fase, KABV, leesassesserings, leesbaarheid, leesbaarheidsindekse, leesprobleme, skoolhandboeke, tekskeuse, Afrikaans Home Language, Afrikaans Huistaal, reading problems, text selection, readability, readability indices, Misindeks